217k views
0 votes
Simplify 5x + 2(x - 3) = -2(x - 1)

User Simap
by
4.9k points

2 Answers

3 votes

Answer:

7x-6=-2x-2 or 5x=4 (depending on how much you have to simplify)

Explanation:

im bad at math but i tried lol

User Alleus
by
5.4k points
3 votes

Answer:

x=8/9

Explanation:

5x+2(x-3)=-2(x-1)

1) Distribute 2 to x and -3:

5x+2x-6=-2(x-1)

2) Distribute -2 to x and -1:

5x+2x-6=-2x+2

3) Combine alike terms:

7x-6=-2x+2

4) Add 2x to both sides:

9x-6=2

5) Add 6 to both sides:

9x=8

6) Divide both sides by 9:

x=8/9

User StanfordNLPHelp
by
5.7k points